Al-Wa‘d as Muhallil of Multi Contract (Ambiguity of Applying Al-Wa’d in Modern Transaction) - Maksum, Muhammad (Institut Agama Islam Negeri Madura, 2016)
Wa’d (the unilateral promise) is an alternative for separate multi contract in one transaction and ribâ that are prohibited with Islamic law. The application of this promise faces difficulty because of difference of principle between unilateral promise that is not binding and the business practice that based on rule of law. The fatwa of DSN, in one side, use both unilateral promise (wa’d) and bilateral promise (muwâ’adah), and other side, consider such as binding in case and not binding in other case. This indicates the difficulty for applying wa’d at the modern contract. Fatwa of DSN has tendency on binding the promise, especially uni-lateral promise. The consequence of this binding is the confusion between promise and contract and the perform of both at the transaction.Copyright (c) 2016 by KARSA. All right reserved DOI: 10.19105/karsa.v24i2.1003